Speciation analysis of Arsenic in fish and rice samples using liquid chromatography-inductively coupled plasma mass spectrometry - Coelho, Inês (2016)
Chemical speciation in foodstuffs is of uttermost importance since it is nowadays recognized that both toxicity and bioavailability of an element depend on the chemical form in which the element is present. Regarding arsenic, inorganic species are classified as carcinogenic while organic arsenic, such as arsenobetaine (AsB) or arsenocholine (AsC), is considered less toxic or even non-toxic. Coupling a High Performance Liquid Chromatographer (HPLC) with an Inductively Coupled Plasma Mass Spectrometer (ICP-MS) combines the power of separation of the first with the selectivity and sensitivity of the second. The present work aims at developing a method, using HPLC-ICP-MS technique, to identify and quantify the chemical species of arsenic present in two food matrices, rice and fish. Two extraction methods, ultrasound and microwave, and different settings were studied. The best method was chosen based on recovery percentages. To ensure that no interconversion of species was occurring, individual spikes of each species of arsenic were made in both matrices and recovery rates were calculated. To guaranty accurate results reference material BCR-627 TUNA FISH, containing certified values for AsB and DMA, was analyzed. Chromatographic separation was achieved using an anion exchange column, HAMILTON-PRP X-100, which allowed to separate the four arsenic species for which standards were available (AsB, dimethylarsenic (DMA), arsenite (AsIII), arsenate (AsV). The mobile phase was chosen based on scientific literature and adjusted to laboratory conditions. Different gradients were studied. As a result we verified that the arsenic species present in both matrices were not the same. While in fish 90% of the arsenic present was in the form of arsenobetaine, in rice 80% of arsenic was present as DMA and 20% as inorganic arsenic.